2023
DOI: 10.3390/ijns9010013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Laboratory Evaluation of Prototype Dried Blood Spot Quality Control Materials for Creatine Kinase-MM Newborn Screening Assays

Abstract: Pilot studies to detect newborns with Duchenne Muscular Dystrophy (DMD) by newborn bloodspot screening (NBS) have been conducted under the New York State Newborn Screening Program (NYS) and are currently in progress as part of the Early Check Program at Research Triangle Institute (RTI) International. The Newborn Screening Quality Assurance Program (NSQAP) at the U.S. Centers for Disease Control and Prevention (CDC) produced a set of seven prototype dried blood spot (DBS) reference materials spiked with varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Emerging approaches for NBS of MPSs using digital microfluidics and fluorescence-based DBS assays have also been described [ 138 ]. There is continuing interest in NBS for Duchenne muscular dystrophy (DMD) with a number of recent reports: demonstration that hospital-based NBS using a two-tiered approach with an enzyme assay for creatine kinase (CK) coupled with targeted NGS for the DMD gene is feasible and can fill the gap until NBS is available [ 139 ]; development of an algorithm for screening and diagnosis of DMD-carrier females, including both NBS and cascade molecular testing of family members as part of the output from a pilot screening project in New York [ 140 ]; recommendations from a pilot for multi-tiered cutoffs as part of the CK enzyme assay based on age at time of specimen collection and birth weight or gestational age, with the possibility that other cutoff determinants may be appropriate (e.g., sex, race/ethnicity, and seasonal temperature) [ 141 ]; and multi-laboratory evaluation of prototype DBS quality control materials for CK-MM isoform assay for NBS [ 142 ]. Interest in NBS for metachromatic leukodystrophy (MLD) and development of an assay for arylsulfatase A (ARSA) activity in DBS leukocytes using liquid chromatography tandem mass spectrometry LC MS/MS [ 143 ] contributed to the development of a NBS testing algorithm [ 144 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging approaches for NBS of MPSs using digital microfluidics and fluorescence-based DBS assays have also been described [ 138 ]. There is continuing interest in NBS for Duchenne muscular dystrophy (DMD) with a number of recent reports: demonstration that hospital-based NBS using a two-tiered approach with an enzyme assay for creatine kinase (CK) coupled with targeted NGS for the DMD gene is feasible and can fill the gap until NBS is available [ 139 ]; development of an algorithm for screening and diagnosis of DMD-carrier females, including both NBS and cascade molecular testing of family members as part of the output from a pilot screening project in New York [ 140 ]; recommendations from a pilot for multi-tiered cutoffs as part of the CK enzyme assay based on age at time of specimen collection and birth weight or gestational age, with the possibility that other cutoff determinants may be appropriate (e.g., sex, race/ethnicity, and seasonal temperature) [ 141 ]; and multi-laboratory evaluation of prototype DBS quality control materials for CK-MM isoform assay for NBS [ 142 ]. Interest in NBS for metachromatic leukodystrophy (MLD) and development of an assay for arylsulfatase A (ARSA) activity in DBS leukocytes using liquid chromatography tandem mass spectrometry LC MS/MS [ 143 ] contributed to the development of a NBS testing algorithm [ 144 ].…”
Section: Resultsmentioning
confidence: 99%
“…This information was used to implement age-related cutoffs for CK-MM [ 284 ]. Addressing the need for external quality control materials, in collaboration with the CDC and RTI International, prototype dried bloodspot quality control materials for CK-MM NBS assays were also evaluated [ 142 ].…”
Section: Resultsmentioning
confidence: 99%
“…A considerable proportion of newborns screened in the first 3 days after birth, when NBS typically occurs, had higher levels of CK-MM relative to the newborns who were screened after 72 h of age, indicating that age-based CK-MM levels must be considered during assay verification and evaluation of options for appropriate NBS algorithms. Multiple cutoffs have been previously proposed by different NBS programs based on variables, including age [ 11 ]. Considering age in NBS algorithm design is significant to optimize both positive and negative predictive values.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of CK-MM in newborn dried blood spots (DBSs) by the recently developed isoform-specific fluoroimmunoassay [#3311-001U, Revvity] has improved the specificity of screening compared to previous screening for total CK (all isoforms, namely -MM, -MB, and -BB, combined). However, because CK-MM is an indirect marker of DMD and can also be elevated because of other causes of muscle damage [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], the risk for false positives remains. Indeed, recent studies have shown that transiently elevated CK-MM in the early newborn period could be a significant cause of false-positive NBS referrals.…”
Section: Introductionmentioning
confidence: 99%